The economics of research, consulting, and teaching quality: Theory and evidence from a technical university - Stefano Bianchini; Francesco Lissoni; Michele Pezzoni; Lorenzo Zirulia (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2014)
We investigate the effect of both research and consulting on higher education teaching quality at the individual level. We propose a theor etical model in which academics allocate limited time between three activities, over a two period horizon, under the assumption of positive spillovers from research to both consulting opportunities and teaching, and of life cycle effects on incentives. Propositions from the model are tested against teaching evaluation data from a mid-sized Italian engineering faculty. We find that research experience improves teaching quality, but only if it does not translate into large consulting opportunities. In that case, research experience provides too strong a disincentive to invest time in teaching, and quality deteriorates .
Keywords: 330; higher education; teaching; academic consulting; research; economics of science